2016
DOI: 10.1038/nature19067
|View full text |Cite
|
Sign up to set email alerts
|

A human neurodevelopmental model for Williams syndrome

Abstract: Summary Williams syndrome (WS) is a genetic neurodevelopmental disorder characterized by an uncommon hypersociability and a mosaic of retained and compromised linguistic and cognitive abilities. Nearly all clinically diagnosed individuals with WS lack precisely the same set of genes, with breakpoints in chromosome band 7q11.231–5. The contribution of specific genes to the neuroanatomical and functional alterations, leading to behavioral pathologies in humans, remains largely unexplored. Here, we investigate ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
163
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(169 citation statements)
references
References 60 publications
4
163
2
Order By: Relevance
“…In particular it is interesting that de novo duplications of the 7q11.23 region is associated with ASD, whereas deletion of the same region causes Williams-Beuren syndrome, characterized increased sociability 163 . Willliams syndrome has been modeled in hiPSC and it has been shown that Willliam syndrome progenitors have increased doubling time and apoptosis, while neurons show increased dendritic spines and synapses compared with typically developing neural cells 164 as well as prolonged repolarization times and a deficit in voltage-activated K+ currents 165 .…”
Section: Induced-pluripotent Stem Cell Models Of Neurodevelopmentamentioning
confidence: 99%
“…In particular it is interesting that de novo duplications of the 7q11.23 region is associated with ASD, whereas deletion of the same region causes Williams-Beuren syndrome, characterized increased sociability 163 . Willliams syndrome has been modeled in hiPSC and it has been shown that Willliam syndrome progenitors have increased doubling time and apoptosis, while neurons show increased dendritic spines and synapses compared with typically developing neural cells 164 as well as prolonged repolarization times and a deficit in voltage-activated K+ currents 165 .…”
Section: Induced-pluripotent Stem Cell Models Of Neurodevelopmentamentioning
confidence: 99%
“…First, current diagnostic criteria for psychiatric disorders are based upon symptomatology alone and do not classify patients according to underlying disease biology ( Diagnostic and statistical manual of mental disorders (5 th edition), 2013); for this reason, recruitment and selection of patients with psychiatric diagnoses frequently yields heterogeneous samples lacking shared disease etiology. Although this problem may be overcome by studying hiPSCs only from individuals with well-defined genetic lesions and/or disease-relevant endophenotypes (e.g., Wen et al, 2014; Lee et al, 2015; Chailangkarn et al, 2016), such an approach necessarily limits the generalizability of any findings to the broader disorder. Second, because hiPSC-derived neurons most resemble fetal brain cells in temporal and spatial patterning (Mariani et al, 2012; Lancaster et al, 2013; Miller et al, 2013; Vera and Studer, 2015), they better model aspects of disease predisposition than the disease-state itself (Brennand et al, 2015).…”
Section: Applications Of Crispr/cas9 Techniques To Human Induced mentioning
confidence: 99%
“…Because single-cell resolution studies have demonstrated somatic mosaicism in both adult human brain (McConnell et al, 2013) and hiPSCs neurons (Erwin et al, 2016), single-cell approaches may be increasingly necessary to query intercellular variability in genomic content and phenotypes (Bardy et al, 2016). Nevertheless, despite these limitations, many groups have already successfully employed hiPSC-based models for the study of neuropsychiatric disorders (e.g., Brennand et al, 2011; Brennand et al, 2015; Chailangarn et al, 2016; Balachandar et al, 2016). …”
Section: Applications Of Crispr/cas9 Techniques To Human Induced mentioning
confidence: 99%
“…Thus, we have demonstrated that iPSC-derived neurons with morphological changes largely comparable to the ones in the postmortem cortex, displayed differences in doubling time of NPCs and calcium transients in response to activity, both of which may underlie morphological changes observed in individual neurons. 27 Although the generation of heterogeneous populations of neuron subtypes and astrocytes from iPSCs in vitro was achieved in our study, they were 2-dimensional and, therefore, less complex, and much less mature compared with our actual sophisticated brains. Thus, 2D neuronal cultures could possibly recapitulate only cellular defects occurring during early stages of brain development and the findings obtained from such models must be cautiously interpreted.…”
Section: Gtf2ird1mentioning
confidence: 99%
“…We have described neuronal phenotypes of NPCs and neurons derived from WS patient together with parallel validation in postmortem neurons. 27 Despite the availability of current protocols for neuronal differentiation, a major concern in disease modeling using iPSC-derived neural cells that could lead to misinterpretation of the findings is the variation in the neuronal populations generated in vitro from each batch of differentiation. We have characterized as much as possible our neuronal culture derived in the study by performing 3 independent analyses.…”
Section: Gtf2ird1mentioning
confidence: 99%